E-MODULE FOR BASIC COMMUNICATION NAVIGATION AND SURVEILLANCE (CNS) - Khoiruman Fadilah, Muhammad; Fatmawati, Fatmawati (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Basic Communication Navigation and Surveillance is one of the courses in the Aviation Communication program. Basic CNS covers the technology that forms the infrastructure for managing and ensuring safe and efficient air traffic. The objective of this final project is to design and create an e-module for Basic CNS as a new, innovative, and engaging learning media to assist in teaching Basic CNS. The e-module will be implemented into the existing Learning Management System at Aviation Polytechnic of Surabaya. The research method used is qualitative descriptive, with data collected through interviews, researcher’s notes, and documentation. The e-module is designed using the ASSURE development method, which includes analyzing learner characteristics, stating objectives, selecting, modifying or designing media, utilizing media, requiring learner responses, and evaluating. The result of this research is an e-module that contains the materials for the Basic Communication Navigation and Surveillance (CNS) course, aligned with the academic syllabus. It includes flipbook-style teaching materials with images, videos, audios, midterm and final exam questions. Each question can be used to deepen the knowledge and understanding of the subject matter